Isu Gender dan Dinamika Hukum Keluarga Iran: Penelitian - Aisyah Auliyar Rahmah Mahyudin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article discusses the issue of gender which is often discussed, and about family law regulated in Iran as one of the countries with the largest Muslim majority among other countries in the world. The things that will be sought in this article include 1. What is the profile of the Islamic Republic of Iran? 2. How is the development of Islamic law in the Islamic Republic of Iran? 3. How is the Religious Court system and family law in the Islamic Republic of Iran? The research method of this article uses a type of library research, by taking materials from books, journals, encyclopedias or so on. This article uses a qualitative approach. The data collection technique for this article is a literature study. The data analysis technique for this article is a qualitative data analysis technique, the data collection process is through recording and notes, literature review. The results of this study are In the Constitutional Revolution of 1905 to 1911, democratic nationalists tried to end the absolute monarchy, the constitution and legal reform. They succeeded in laying the foundation for an independent judiciary and a parliament with legislative powers. The despotic but modernizing Pahlavi Shahs (1925-1979) retained (though largely abandoned) both the constitution and the parliament, limited the power of the Shia clerics, and dispensed with sharia in all areas of family law in favor of a secular legal system inspired by European codes.